Industrial Training Report: The office of library and knowledge management of Universiti Malaysia Kelantan / Siti Sarah Mohamad Nasir - Mohamad Nasir, Siti Sarah (Faculty of Information Management, 2014)
The purpose of this practical training report was undertaken to record the entire task that had been taken during practical training for almost 5 months. It covers several parts about UMK and the UMK Library includes introduction to organization, vision, mission, objective and others. Besides that, it also covers about facilities and something that related with the UMK Library. This report also cover about the special project that was done during practical training. Apart from that, this report also supported with photo as prove, the lesson learnt during practical training and also the comment and recommendation about this library.